2021
DOI: 10.1021/acsnano.1c04194
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotubes for Radiation-Tolerant Electronics

Abstract: Electronics for space applications have stringent requirements on both performance and radiation tolerance. The constant exposure to cosmic radiation damages and eventually destroys electronics, limiting the lifespan of all space-bound missions. Thus, as space missions grow increasingly ambitious in distance away from Earth, and therefore time in space, the electronics driving them must likewise grow increasingly radiation-tolerant. In this work, we show how carbon nanotube (CNT) field-effect transistors (CNFE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…57 This is most likely due to the fact that after the irradiation process, carboxyl (O�C− OH) groups change into carboxylate O−C�O− groups. 58 This factor can also affect (induce) the increase in sp 3 hybridization.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…57 This is most likely due to the fact that after the irradiation process, carboxyl (O�C− OH) groups change into carboxylate O−C�O− groups. 58 This factor can also affect (induce) the increase in sp 3 hybridization.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A prolonged exposure to ionizing radiation damages and ultimately destroys functional semiconductor materials in electronic devices, limiting their lifetime. Irradiation exposure can cause chemical bonds within a material to break, altering their morphological and structural characteristics, which in turn can cause it to swell, polymerize, cause corrosion, cause quality loss, contribute to cracking, or otherwise change its desired mechanical, optical, or electronic properties. Achieving high stability under intense ionizing irradiation is of great importance for many applications, ranging from nuclear power reactors to electronics for the emerging space industry. Satellites orbiting the Earth experience both electron and proton bombardment. As scientific and commercial space missions have rapidly become more and more ambitious, the employed functional electronic materials have to meet growing requirements for their radiation resistance as well.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33] As is well-known, complementary metal-oxide-semiconductor (CMOS) technology, which comprises both P-type and N-type TFTs working complementarily, is the most successful circuit style for modern ICs because of its low static power dissipation and high noise margin [34][35][36] and is thus preferred in low-power and robust paper-based electronics. Although many recent studies have shown that semiconducting single-walled carbon nanotubes (CNTs) are one of the ideal materials for achieving high-performance, flexible and radiation-tolerant CMOS ICs, [37][38][39][40][41][42][43][44] few works have fabricated CNT CMOS ICs on paper-based substrates, especially using E-mode CNT CMOS TFTs with low power consumption. Therefore, the fabrication of low-power-consumption CMOS ICs on paper substrates is famously challenging, which has hindered the development of paper-based electronics.…”
Section: Research Articlementioning
confidence: 99%
“…[ 24 ] Recently, the local bottom gate has been proven to be an ideal structure resistant to radiation. [ 38 ] For these reasons, our paper‐based E‐mode CNT TFTs and ICs with ultrathin AlO X (4.2 nm) dielectrics (high capacitance of 1.54 μF cm −2 ) and local Al gates are also expected to have excellent radiation‐hardened properties.…”
Section: Radiation Tolerance Of Cnt Cmos Tfts and Icsmentioning
confidence: 99%
“…Furthermore, two additional advantages, i.e., energy efficiency and low-temperature stability, enable CNT transistors to further meet the strict and harsh requirements for ICs used in deep space exploration [10][11][12][13] . Recently, great advances in radiation-hardened CNT ICs have been achieved, but these works mainly focused on the total ionizing dose (TID) effect 8,9,14 , which is not sufficient to characterize the comprehensive radiation tolerance performance of an IC in the real space radiation environment. Compared to the TID effect, single event effects (SEEs) 15 and the displacement damage (DD) effect 16 are at least equally important in practical applications but are rarely studied in CNT-based transistors and ICs because they are more difficult to measure due to the challenges from the requirements on irradiation source as well as the complex circuits and electromagnetic environment.…”
mentioning
confidence: 99%